Active opioid use does not attenuate the humoral responses to inactivated influenza vaccine. Issue 11 (8th March 2016) - Moroz, Ekaterina; Albrecht, Randy A.; Aden, Brandon; Beeder, Ann Bordwine; Yuan, Jianda; García-Sastre, Adolfo; Edlin, Brian R.; Salvatore, Mirella
Abstract: Background: Influenza vaccination is recommended for vulnerable individuals, including active drug users, to prevent influenza complications and decrease influenza spread. Recent studies suggest that opioids negatively regulate immune responses in experimental models, but the extent to which opioid use will affect the humoral responses to influenza vaccine in humans is unknown. This information is critical in maximizing vaccination efforts. Objective: To determine whether there is a difference in antibody response after influenza vaccination in heroin or methadone users compared to control subjects. Methods: We studied active heroin users, subjects on methadone maintenance treatment (MMT) and subjects that did not use any drugs before and 1 and 4 weeks after vaccination with trivalent influenza vaccine (TIV). We measured hemagglutination inhibition and microneutralization titers, and we compared geometric mean titers (GMT), and rates of seroprotection and seroconversion for each of the vaccine strains among the 3 groups of subjects. Results: Heroin users, subjects on MMT and non-user controls mount a similarly robust serologic response to TIV. GMT and rates of seroprotection and seroconversion were not significantly different among groups. Conclusion: Our results suggest that opioid use do not significantly alter antibody responses to influenza vaccine supporting the vaccination effort in these populations.